Secondary metabolites synthesized by Stemphylium lycopersici and Fulvia fulva, necrotrophic and biotrophic fungi pathogen of tomato plants - Medina, Rocío (2019)
The aim of this work was to study the volatile organic compounds (VOCs) profile and diffusible secondary metabolites (SMs) of Stemphylium lycopersici and Fulvia fulva, two fungal pathogens of tomato. S. lycopersici synthesizes and releases quantitatively more VOCs than F. fulva, probably due to the different type of interaction that each fungus establishes with tomato; nevertheless, F. fulva synthesized a specific and more diverse spectrum of VOCs. S. lycopersici released VOCs that triggering cell death in tomato leaves. Also, F. fulva synthesized an ample array of SMs but their biological roles remain to be elucidated.